2015
DOI: 10.1053/j.gastro.2015.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Gastric Emptying Is Associated With Early and Long-term Hyperglycemia in Type 1 Diabetes Mellitus

Abstract: Background and Aims After the Diabetes Control and Complications Trial (DCCT), the Epidemiology of Diabetes Interventions and Complications (EDIC) study continued to demonstrate persistent benefit of prior intensive therapy on neuropathy, retinopathy, and nephropathy in type 1 diabetes mellitus (DM)., The relationship between control of glycemia and gastric emptying (GE) is unclear. Methods We assessed GE with a 13C-spirulina breath test and symptoms in 78 participants with type 1 diabetes at year 20 of EDIC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
79
2
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(96 citation statements)
references
References 46 publications
1
79
2
4
Order By: Relevance
“…Indeed, it has also been shown that, among 78 patients with type 1 diabetes mellitus followed for 20 years, delayed gastric emptying was associated with early and long-term hyperglycemia. 9 Moreover, gastric emptying can impact glycemic control; for example, in patients with type 2 diabetes not on insulin, delayed gastric emptying in the absence of symptoms may potentially be advantageous in relation to postprandial glycemic control, 10 and this is the basis for treatment with amylin analogs or GLP-1 receptor agonists in patients with type 2 diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it has also been shown that, among 78 patients with type 1 diabetes mellitus followed for 20 years, delayed gastric emptying was associated with early and long-term hyperglycemia. 9 Moreover, gastric emptying can impact glycemic control; for example, in patients with type 2 diabetes not on insulin, delayed gastric emptying in the absence of symptoms may potentially be advantageous in relation to postprandial glycemic control, 10 and this is the basis for treatment with amylin analogs or GLP-1 receptor agonists in patients with type 2 diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Gastric emptying times are demonstrated to be slower in Type I diabetic patients and intestinal dysmotility is prominent in pediatric patients who've suffered from gastroschisis, Hirschsprung disease or infantile pyloric stenosis where there may be abnormal or altered expression of the interstitial 'pacemaker' cells [85][86][87]. Protein binding may be altered in children with higher levels of circulating displacers as in children with amino acid n-acyltransferase deficiency, which manifests with defects within the bile acid synthesis or patients on chronic total parenteral nutrition wherein cholestasis is a frequently encountered problem.…”
Section: Secondary Factors Influencing Dispositionmentioning
confidence: 99%
“…This type of diabetes is generally found in children and young adults, even though it can appear at any age. [9] explains that the environmental factors such as foods, viruses and toxins would play a major role in the causes of type 1 diabetes. However the exact reason for their role has not yet found.…”
Section: Type 1dmmentioning
confidence: 99%